Pengenalan Literasi Keuangan Syariah Pada Anak Usia Dini Di KB Al Fatih Jiwanalan - Faida Sulistiya; Assa Hiyyah; Bibit Laeli Febriani; Siti Fatimah (IAINU Kebumen, 2022)
An understanding of financial literacy is needed to educate people to be aware andunderstand how to manage finances wisely and according to their needs. This service aims tointroduce sharia literacy to children this age at KB Al Fatih Jiwanalan. This service is carriedout for 5 days in March 2022. The introduction of Islamic financial management and literacyat KB Al Fatih Jiwanalan includes several scopes, namely the introduction of various formsand nominal currencies, the concept of buying and selling, the concept of bad practices infinance, and saving concept. The distinctive character of implementing the introduction ofIslamic financial management and literacy at KB Al Fatih Jiwanalan is to integrate it with thebasis of Islamic Sharia and interesting learning media such as illustrated story books,educational videos, and loose part game tools